2020
DOI: 10.1002/cad.20332
|View full text |Cite
|
Sign up to set email alerts
|

Historical Trauma and American Indian/Alaska Native Youth Mental Health Development and Delinquency

Abstract: Health disparities in American Indian/Alaska Native (AI/AN) youth are well documented in the literature, as AI/AN youth appear to be more likely to experience trauma and engage in high‐risk behavior, such as substance misuse and risky sexual behavior. These youth also appear disproportionally affected by the criminal justice system. Scholars contend that much of these disparities can be traced back to the history of colonization of Indigenous peoples and the transgenerational effects of forced suppression of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 53 publications
(92 reference statements)
1
11
0
Order By: Relevance
“…We also found that Native Americans had the highest odds of a new mental health ED visit compared to Whites. This is notable given the low overall prevalence of Native Americans in our sample but consistent with the current literature, which shows that Native American communities suffer from historical trauma, higher rates of substance use, and Native American youth have high rates of depression 32 . We find Hispanics and Asians have decreased mental health visits.…”
Section: Discussionsupporting
confidence: 89%
“…We also found that Native Americans had the highest odds of a new mental health ED visit compared to Whites. This is notable given the low overall prevalence of Native Americans in our sample but consistent with the current literature, which shows that Native American communities suffer from historical trauma, higher rates of substance use, and Native American youth have high rates of depression 32 . We find Hispanics and Asians have decreased mental health visits.…”
Section: Discussionsupporting
confidence: 89%
“…A review of the extant literature about American Indian students suggests that of the little research that does exist, considerable attention has been paid to problems, challenges and obstacles that these students have encountered in their educational and personal lives. Indeed, the negative features of students’ educational experiences, outcomes and mental health have been extensively studied and documented (Garcia, 2020; Riser et al , 2019). From data detailing high rates of school dropout (Stetser and Stillwell, 2014), to studies documenting elevated suicidal behavior (Burrage et al , 2016), to problems associated with service delivery due to mistrust of providers (Call et al , 2006), the existing tradition of scholarship has focused almost exclusively on negative events and circumstances of American Indian youth and their families.…”
Section: Conceptual Frameworkmentioning
confidence: 99%
“…The pandemic adds a "spectacle" to the silenced but well-documented intergenerational trauma among these communities. It adds a visual display of the historical experiences of trauma from slavery, displacement, colonization and genocide that are "passed on" from one generation to the next through a combination of biological, behavioral and psychological processes (Chavez-Dueñas et al 2019;Estrada 2009;Garcia 2020;Landor and McNeil Smith 2019;O'Neill et al 2018;Yehuda and Lehrner 2018). Significantly, research highlights the role of structural factors that play into the cycle of continued trauma, including lack of access to adequate and preventative healthcare and the chronic stress associated with social disadvantage and racism (AAFP 2019;Scorza et al 2019;Trent, Dooley, and Douge 2019).…”
Section: Truth and Reconciliation Commissionmentioning
confidence: 99%